Relationship between lipoprotein (a) and subclinical carotid atherosclerosis in asymptomatic individuals - França, Victor; Gomes, Érica Ivana Lázaro; Campos, Edite Vieira Silva de; Zago, Vanessa Helena de Souza; Nunes, Valéria Sutti; Faria, Eliana Cotta de (Clinics, 2022)
Background: This study aimed to evaluate the associations between Lipoprotein (a) ‒ Lp(a) levels and carotid Intima-Media Thickness (cIMT) and with carotid plaques in healthy subjects because of previous contradictory data.Methods: A total of 317 healthy normolipidemic subjects (20‒77 years old) were selected. The cIMT and atherosclerotic plaques were determined by B-mode ultrasonography. Mann-Whitney tests were performed to compare the groups according to Lp(a) levels and to explore the associations between Lp(a), carotid plaques, and cIMT, logistic and linear regression analyses were performed.Results: Studied population (51% females, median age 43 years old) presented carotid plaques and cIMT ≥ 0.9 mm in 23% and 18% of the participants, respectively. The group with Lp(a) levels > 30 mg/dL presented significantly higher age and atherosclerotic plaques. Indeed, multivariate linear regression analysis showed a significant association between Lp(a), age, and race. On the other hand, logistic regression analysis demonstrated that the subjects with Lp(a) > 30 mg/dL have a significantly high risk of carotid plaques.Conclusion: The data from the present study indicate that Lp(a) levels above 30 mg/dL contribute to the development of carotid plaques even in apparently healthy participants.